1980
DOI: 10.1148/radiology.137.1.7422844
|View full text |Cite
|
Sign up to set email alerts
|

Focal nodular hyperplasia of the liver as established by 99mTc sulfur colloid and HIDA scintigraphy.

Abstract: Three cases of focal nodular hyperplasia of the liver are reported, presumably associated with the long-term use of oral contraceptives. Special reference is made to hepatobiliary scintigraphy with 99mTc diethyl-IDA, and the cause of the observed findings is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

1983
1983
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 0 publications
0
5
0
6
Order By: Relevance
“…However, contrary to expectations, several studies showed that 30–36% of FNH have decreased uptake [32,64,65]. Herman et al [66] used the 99m Tc-sulfur-colloid scan preoperatively for the diagnosis of FNH (n = 13) and HCA (n = 10).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, contrary to expectations, several studies showed that 30–36% of FNH have decreased uptake [32,64,65]. Herman et al [66] used the 99m Tc-sulfur-colloid scan preoperatively for the diagnosis of FNH (n = 13) and HCA (n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…The hepatobiliary tracer 99m Tc-mebrofenin (HIDA) is, like the hepatobiliary MR contrast agents, taken up by functional hepatocytes and excreted into the bile [64]. Since biliary drainage in FNH is reduced compared to normal liver parenchyma, the tracer is retained and visible as a hot spot on delayed images [65].…”
Section: Resultsmentioning
confidence: 99%
“…The lesion may be either isodense or hypodense [4]. However, according to a recent report, as many as 44% of nine tumors were undetectable on the basis of tissue attenuation differentials, and the detection of the lesion was not improved by the use of intravenous contrast material [26].…”
Section: Discussionmentioning
confidence: 99%
“…Der Fokus liegt dabei auf der Positronenemissionstomografie in Kombination mit der Computertomografie (PET/CT). Die hepatobiliäre Funktionsszintigrafie unter Verwendung von 99m Technetium markierten Imino-diacetat-Verbindungen, welche auch zur Charakterisierung verschiedener Lebertumore dienen kann [11], liegt außerhalb des Fokus dieser Arbeit. Diesbezüglich wurde jedoch insbesondere in den letzten Jahren der Stellenwert zur Beurteilung der Leberfunktion im Rahmen der Radioembolisation primärer und sekundärer Lebertumore gezeigt [12,13,14].…”
Section: Introductionunclassified